Clinical study of recurrent mild encephalitis/encephalopathy with a reversible splenial lesion in two cases - Jiao Xue; Chongfeng Duan; Guizhi Xu; Ying Zhang; Zhenfeng Song; Zhi Yi; Chengqing Yang; Fei Li; Kaixuan Liu; Hongshan Zhao; Xuejun Liu (BMC, 2022)
Abstract Background Mild encephalitis/encephalopathy with a reversible splenial lesion (MERS) has been reported worldwidely. However, the data about recurrent cases is limited. We aimed to analyze the clinical and radiographic features of recurrent MERS, and its possible mechanisms. Case presentation Two patients with clinically recurrent MERS were reported here, exhibiting neurological symptoms such as limbs weakness and numbness, stand/walk unsteadily, slurred speech and irritability, and typical lesions in the corpus callosum and white matter. One of them experienced another four episodes with a similar clinical course and magnetic resonance imaging findings over a period of 10 years. The Na levels in the present two patients were normal. Discussion and conclusion Combined with the patients reported previously, recurrence could be seen in both MERS type 1 and type 2 patients, from two to multiple times, with the latter possibly more common. It suggested that some genetic factors might be involved in MERS, especially for MERS type 2 or familial MERS.